Evaluating chain-of-thought prompting in a GPT chatbot for BCID2 interpretation and stewardship: how does AI compare to human experts? - Daniel M. Tassone; Matthew M. Hitchcock; Connor J. Rossier; Douglas Fletcher; Julia Ye; Ian Langford; Julie Boatman; J. Daniel Markley (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract